1995
DOI: 10.3109/08977199509036883
|View full text |Cite
|
Sign up to set email alerts
|

Colocalisation of Vascular Endothelial Growth Factor and Its Flt-1 Receptor in Human Placenta

Abstract: Vascular endothelial growth factor (VEGF) is an angiogenic protein which acts on both endothelial and trophoblast cells. In first trimester placenta, VEGF immunoreactive protein was detected in cytotrophoblast shell suggesting a role in the regulation of cytotrophoblast growth and differentiation as they also expressed VEGF receptor (flt-1) protein. VEGF and flt-1 immunoreactive proteins were expressed in Hofbauer cells within the villous mesenchyme, macrophages and in maternal decidual cells while weak VEGF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(119 citation statements)
references
References 20 publications
8
103
0
8
Order By: Relevance
“…In brief, after incubation with rabbit anti-human NF-B, an HRP-conjugated goat-anti-rabbit Capillaries that were stained along the circumference were recorded as positive. VEGF, VEGF-R1, VEGF-R2, TIE-2, and HIF-1␣ were expressed on all endothelial cells (22,(37)(38)(39). Therefore, the intensity of staining was measured with a three-step semiquantitative scale (magnification ϫ200) as weak (ϩ1), moderate (ϩ2), or strong (ϩ3) (40)…”
Section: Methodsmentioning
confidence: 99%
“…In brief, after incubation with rabbit anti-human NF-B, an HRP-conjugated goat-anti-rabbit Capillaries that were stained along the circumference were recorded as positive. VEGF, VEGF-R1, VEGF-R2, TIE-2, and HIF-1␣ were expressed on all endothelial cells (22,(37)(38)(39). Therefore, the intensity of staining was measured with a three-step semiquantitative scale (magnification ϫ200) as weak (ϩ1), moderate (ϩ2), or strong (ϩ3) (40)…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported increased VEGFR-1 levels in cases with preeclampsia (1,13,(35)(36)(37)(38). It has also been suggested that high levels of sVEGFR-1 inhibits angiogenesis by antagonising the effects of VEGF and PlGF (39,40). It has also been shown that sVEGFR-1 levels positively correlate with the severity of preeclampsia (1,9).…”
Section: Discussionmentioning
confidence: 83%
“…Those macrophages will express angiogenic growth factors and, as they appear early, they suggest a paracrine role in the initiation of vasculogenesis. Angiogenic growth factors are also expressed by the maternal decidua and macrophages mediating the trohpoblast invasion [Ahmed et al, 1995]. In the meanwhile since the uterus and its contents demand an increased supply of blood during pregnancy, its vasculature undergoes three main adaptative changes: vasodilation, increased permeability, and growth and development of new vessels.…”
Section: Vessel Growth and Angiogenesismentioning
confidence: 99%